Catalyzing financial inclusion: Using incentives to promote mobile money use in Ethiopia - de Brauw, Alan; Gilligan, Daniel O.; Herskowitz, Sylvan; Roy, Shalini (International Food Policy Research Institute, 2024)
Mobile money can be a vehicle for improving financial access, particularly among disadvantaged populations. For mobile money systems to play this role, though, members of disadvantaged groups must both enroll in and begin to use mobile money systems. In this paper, we describe a randomized trial conducted in collaboration with a bank in Somali region, Ethiopia, that attempted to stimulate use among recent mobile money enrollees in areas near refugee camps. We provide one group with a small transfer to their mobile money account and another group is told they will receive a small transfer if they first make three transactions of any type within a promotional period. The unconditional transfer induces a 9.3 percentage point increase in customers making at least one transaction, while the conditional transfer has no significant effect. The effect is larger among men, but there is evidence that it also induces use among women.